Muscle Function and Thickness Are Not Associated with Responsiveness to Post-Activation Performance Enhancement - Fontanetti, Gabriel [UNESP]; Barreto, Renan Vieira [UNESP]; Junior, Rubens Correa [UNESP]; Mantovani, Guilherme Beneduzzi [UNESP]; Denadai, Benedito Sérgio [UNESP]; Greco, Camila Coelho [UNESP]; Lima, Leonardo Coelho Rabello de [UNESP] (MDPI, 2023)
There is great variability in responsiveness to post-activation performance enhancement (PAPE). Factors such as greater expression of type II muscle fibers and experience with strength training are associated with greater responsiveness to PAPE. We investigated whether there is an association between markers of muscular function and morphology and responsiveness to PAPE in untrained individuals. Sixty-six active men (22 ± 2 years, 74 ± 11 kg, and 172 ± 27 cm) participated in the study. Their countermovement jump (CMJ) heights were measured before and four minutes after a pre-activation protocol consisting of five squats with a 5RM load. Isometric knee extensor peak torque (IPT), CMJ power (POCON), and thickness of the vastus lateralis muscle (VLMT) of the participants were also determined in an unpotentiated condition. Change in CMJ height (ΔCMJ) following the pre-activation protocol was calculated and its associations with baseline CMJ height (CMJCON), POCON, IPT, and VLMT were tested. Linear stepwise multiple regression models were also applied to screen for predictors of ΔCMJ among the dependent variables. No significant change (p = 0.28) in CMJ height was observed after the PA protocol (pre: 30.8 ± 5.1 cm; post: 31.0 ± 5.5 cm). No significant associations (p > 0.05) were found between ΔCMJ and IPT, VLMT, POCON, and CMJCON (r = 0.29, 0.18, 0.09, and 0.01, respectively). Linear stepwise multiple regression analyses did not result in any significant models for ΔCMJ prediction. Although we confirmed the high individual variability in response to PA, no associations between neuromuscular performance/morphology and responsiveness to PAPE were found.
Keywords: countermovement jump; human performance; jump performance; muscle power; post-activation performance enhancement; strength